Educational Resilience Amidst COVID-19: Global Insights and Strategies - Ziwei Wang (New Zealand Journal of Teachers' Work)
This research overview investigates the global impact of the COVID-19 pandemic on education, focusing on challenges encountered during the shift to online learning. Drawing insights from studies in New Zealand, Oman, Malaysia, and Germany, the overview explores diverse experiences of educators and students. The abrupt transition to online learning revealed significant challenges, as indicated by various studies. Opportunities for positive changes in education systems are emphasized, advocating for a reimagining of education through innovative practices. This literature review identifies practical and effective strategies for online education, including fostering a sense of community, providing personalized support and feedback, accommodating divers e-learner needs, and considering the learning environment and cognition. Insights from various studies underscore the importance of these practices in overcoming challenges and improving online education quality.